Renewable fatty acid ester production in Clostridium - Jun Feng (Nature Portfolio, 2021)
Esters can be used as fuels and specialty chemicals for food flavoring, cosmetic and pharmaceutical industries. Here, the authors systematically engineer clostridia, including discovery and deletion of prophages to increase strain stability, for the production of butyl acetate and butyl butyrate from corn stover at low cost.